Enhanced IRES activity by the 3'UTR element determines the virulence of FMDV isolates - García Núñez, María Soledad (2014)
A reverse genetics approach was used to identify viral genetic determinants of the differential virulence displayed by two field foot-and-mouth disease virus (FMDV) strains (A/Arg/00 and A/Arg/01) isolated in Argentina during the 2000-2001 epidemics. A molecular clone of A/Arg/01 strain and viral chimeras containing the S-fragment or the internal ribosome entry site (IRES) of A/Arg/00 in the A/Arg/01 backbone were constructed and characterized. The IRES appeared as a determining factor of the lower level of A/Arg/00 replication in cell culture. High-throughput RNA probing revealed structural differences between both IRESs. Translation experiments using either synthetic viral RNAs ( in vitro) or bicistronic plasmids ( in vivo) showed that these IRESs' activities differ when the viral 3' untranslated region (UTR) is present, suggesting that their function is differentially modulated by this region. This work provides experimental evidence supporting the role of the IRES-3'UTR modulation in determining the level of FMDV replication in field strains.